Development of Tetracycline-Resistant Staphylococcus aureus in Gnotobiotic Mice - Bornside, George H. (1972)
Germ-free mice were colonized with a pigmented, tetracycline-sensitive strain of Staphylococcus aureus and maintained in flexible plastic isolators. Treatment of the gnotobiotic mice with oral tetracycline (20 mg/ml) resulted in the development of staphylococci resistant to tetracycline (5 μg/ml or higher). Resistant staphylococci did not appear in feces until several days after exposure of mice to the antibiotic and persisted for as long as specimens were collected (64 days subsequently). Resistance developed after a single exposure of gnotobiotes to antibiotic. Resistant staphylococci were present in the intestinal tracts of mice at counts of 10(3) per g of contents, whereas sensitive organisms coexisted at counts of 10(5) to 10(11) per g. Resistant staphylococci were isolated only from treated mice and not from untreated mice in adjacent cages. Initial colonization of germ-free mice with sensitive staphylococci interfered with subsequent colonization by resistant staphylococci and provided an example of bacterial interference. Resistance to tetracycline was not associated with resistance to chloramphenicol, penicillin, ampicillin, erythromycin, streptomycin, or kanamycin. Hydrolysis of gelatin was the only biochemical characteristic in which isolates varied but was not correlated with resistance to tetracycline or pigmentation of colonies. A nonpigmented, gray variant of S. aureus appeared in all specimens after colonization with the original, pigmented strain. Only the nonpigmented strain was obtained from gnotobiotes colonized with the nonpigmented variant. Contact between bacteria and antibiotic in the intestinal tract of gnotobiotes was considered to be essential for the development of tetracycline-resistant staphylococci.